Nuclear S-nitrosylation impacts tissue regeneration in zebrafish - Gianfranco Matrone (Nature Portfolio, 2021)
The role of the post-translational modifications in tissue regeneration is still not clearly understood. Here, the authors show that many nuclear proteins change S-nitrosylation state in the regenerating zebrafish tailfin, highlighting the importance of Kdm1a S-nitrosylation in the repair process.